The relationship between arthritis and mild cognitive impairment in different obese metabolic heterogeneity populations-the mediating role of depression - Li, Chen; Chang, Yitie; Cui, Jingxuan; Wang, Zhetian; Zeng, Linru (Frontiers in Nutrition, 2026)
ObjectiveThe purpose of this study is to investigate whether depression may mediate the association between arthritis and mild cognitive impairment (MCI) in diverse BMI-based obese populations with multi-parameter metabolic signatures including insulin resistance, inflammatory markers, and lipid metabolism indices.MethodsThe relationships between arthritis, MCI, and depression were investigated in a large-scale study that used logistic regression, subgroup analyses, and mediation analyses. The participants in the study came from obese individuals classified into distinct metabolic obesity phenotypes based on insulin resistance, inflammatory markers, and lipid metabolism.ResultsArthritis is positively correlated with MCI (OR = 1.86, 95% CI = 1.60–2.17, p < 0.001), especially in the metabolically unhealthy overweight/obesity population (OR = 2.27, 95% CI = 1.73–2.97, p < 0.001), and depression plays a mediating role in the relationship between arthritis and MCI in this population (proportion of mediation: 17.5%).ConclusionThe results of this study highlight the potential clinical value of an integrated management strategy combining metabolic regulation, anti-inflammatory treatment, and routine depression screening in obese patients with arthritis to reduce the risk of cognitive decline.